Strategi Peningkatan Daya Saing Kopi Liberika di Kabupaten Kepulauan Meranti - Nurman Nurman; Elfi Susanti; Lintang Nur Agia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Marketing management is one of the main activities carried out by the company to maintain the sustainability of the company, to develop, and to make a profit. The purpose of this study is to compare the traditional marketing system that is already running with the marketing partnership formed in aspects of marketing channels, marketing practices and marketing efficiency. The analysis used in this research is to use marketing margins. The results of this study indicate that there are three marketing channels available in the liberika coffee industry in the Meranti islands. Marketing practices so far have not been used by farmers, this can be seen from the profit margin obtained by large traders amounting to 1.47%. And from the efficiency of liberika coffee marketing is far from efficient because it has to go through a long process before reaching the final consumer. Keywords: Marketing Channels, Marketing Management, competitiveness